Pengaruh Strategi Segmenting, Targeting, Positioning terhadap Persepsi Deposan di Bank bjb Kantor Cabang Majalaya - Faisal Rakhman; Eneng Eli Siti Solihat (Masoem University, 2022)
This study aims to determine how much influence the Segmenting Strategy, Targeting, Positiong on the Perception of Depositors at Bank BJB KC Majalaya. The object of research is the Perception of Depositors of Bank BJB KC Majalaya. The method used is an associative quantitative method. The type of data used is primary data which is processed using the Statistic application, and uses data collection techniques in the form of observation, interviews, questionnaires, and literature studies as a complement. The population in this research is Bank BJB KC Majalaya depositors in 2020 with a sample of 71 customers. The results of this study indicate that there is a significant effect between Segmenting on Depositors' Perceptions with the t-test where the value of tcount > ttable (4,846>1,668), there is a significant effect between Targeting on Depositors' Perceptions tcount> ttable (7,602> 1,668), there is a significant effect between Positioning on Depositors' Perceptions tcount > ttable (7,576>1,668), and there is a simultaneous significant influence between Segmenting, Targeting, Positioning on Depositors' Perceptions with the results of the F test where Fcount > Ftable (19,097 > 2.17)).